Differential effects of naloxone on postictal depression - Velísek, L; Mares, P (Epilepsy research, 1992)
The influence of naloxone on the duration of the postictal depression was determined in 2 seizure models in the adult rats: hippocampal afterdischarges and maximal electroshock. For testing the intensity of postictal depression 2 subsequent stimulations were used. The interstimulation intervals were 3, 5, 10 and 60 min. Using interstimulation intervals 3, 5 and 10 min there was marked depression of the afterdischarge duration. Wet dog shakes accompanying hippocampal afterdischarges were suppressed only in 3- and 5-min intervals. Naioxone (1 mg/kg i.p.) abolished the suppression of afterdischarges when 10-min interstimulation interval was used. In maximal electroshock seizures where the duration of tonic flexion and extension was determined, no postictal depression was registered nor were any effects of naloxone present. The results suggest a limited role of the mu opioid receptor system in the late phases of postictal depression following hippocampal stimulation and different effects of the mu opioid system in tonic flexion/extension and behavioral depression induced by maximal electroshock.
Keywords: Naloxone; Models, Neurological; chování zvířat; modely neurologické; Epilepsies, Partial; Electric Stimulation; Rats, Inbred Strains; krysa rodu Rattus; Hippocampus; elektrický šok; elektroencefalografie; zvířata; Electroshock; hipokampus; epilepsie parciální; Male; naloxon; Electroencephalography; Rats; Animals; elektrická stimulace; mužské pohlaví; Behavior, Animal; inbrední kmeny potkanů